Faktor-Faktor Yang Mempengaruhi Minat Wajib Pajak Dalam Menggunakan Sistem E-Filling - Mardiana Mardiana; Pipit Nursaputri; Ria Dwi I’zzaty (IJAcc, 2020)
The purpose of this research is to examine the factors affecting interests of taxpayers in using efiling facility. The independent variables of this research are perceived usefulness, perceived ease of use, security and privacy, complexity, readiness technology taxpayers information and human resources. Data used in this research is primary data by using questionnaires. Respondent are the Individual Taxpayers who used e-filing.This research used multiple linear regression analysis that involved 108 respondents. The results show that: (1) perceived usefulness affects positively the intention to use E-filing, (2) perceived ease of use affects positively the intention to use E-Filing, (3) security and privacy affects positively the intention to use E-Filing, (4) complexity affects negatively the intention to use E-filing, (5) Readiness Technology Taxpayers Information affects positively the intention to use E-Filing (6) Human Resources affects positively the intention to use E-Filing